Projected Capacitive Touch A Practical Guide for Engineers - Gray, Tony.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book covers ALL aspects of projected capacitive touch sensors including basic principles, the physics of PCAP, capacitance measurements, touch sensor materials and construction, electrical noise, software drivers, and testing. It is targeted at working engineers who are implementing touch into their products as well as anyone else with an interest in how touch screens work. · Offers readers the first book on the use of projected capacitive (PCAP) touch technology for touch screens; · Explains not only how PCAP touch works, but also addresses the implementation details an engineer needs when incorporating PCAP into their product; · Includes explanations of different cover lens materials, cover lens coatings, software drivers, touch testing, and many other areas of general knowledge that would be useful to a design engineer.
Introduction -- Overview of Touch Technologies -- Projected Capacitive Touch Basics -- Self Capacitance -- An Electrostatic Analysis of PCAP -- Capacitance Measurement -- Transparent Conductors -- Electrode Patterns -- Patterning Techniques -- Perimeter Traces and Tails -- Sensor Stackups -- LCD Integration -- Cover Lenses, Films, and Coatings -- Touch Controllers -- Electrical Noise -- Stylus and Gloves -- Water Immunity -- Palm and Touch Suppression -- PCAP Buttons -- Communication Interfaces, Operating Systems, and Drivers -- Gesture Engines -- Automated Testing.
Keywords: Electronic circuits; Electronics; Electronic Circuits and Systems; Electronics and Microelectronics, Instrumentation